2009
DOI: 10.1007/s10616-009-9246-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved reproducibility in preparing precision-cut liver tissue slices

Abstract: Precision-cut liver tissue slices (PCLS) have been used for decades to study pharmacological metabolism as well as toxicology and efficacy of novel substances on primary material under standardized conditions. Slicing of primary liver tissue has been done using different slicing machines. Since there has been great variability in the results, we sought to compare the reproducibility of tissue slices generated using the newly developed Leica VT1200 S vibrating blade microtome with Vibrocheck (LV) and the Krumdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…Most research groups that successfully prepare and use precision-cut liver slices use the Krumdieck slicer, Vitron slicer or Leica VT1200 S microtome (Krumdieck et al 1980; de Graaf et al 2010; Parrish et al 1995; Zimmermann et al 2009). Recently, the EMS-4000 tissue slicer was introduced, which is mainly used to prepare lung slices (Khan et al 2010a); however, others have performed pilot experiments with rat liver and they have shown that viable PCLS can be prepared (M.H.…”
Section: Liver In Vitro Models In Pharmacology Toxicology and Basic mentioning
confidence: 99%
“…Most research groups that successfully prepare and use precision-cut liver slices use the Krumdieck slicer, Vitron slicer or Leica VT1200 S microtome (Krumdieck et al 1980; de Graaf et al 2010; Parrish et al 1995; Zimmermann et al 2009). Recently, the EMS-4000 tissue slicer was introduced, which is mainly used to prepare lung slices (Khan et al 2010a); however, others have performed pilot experiments with rat liver and they have shown that viable PCLS can be prepared (M.H.…”
Section: Liver In Vitro Models In Pharmacology Toxicology and Basic mentioning
confidence: 99%
“…An alternative to a Weck microtome is a vibrating microtome, which can reproducibly generate thinner slices from firm but not soft tissues (cf 10 ), but is much slower. Very thin slices (100–200 μm) may show a proportionately larger wounding response and are more fragile.…”
Section: Notesmentioning
confidence: 99%
“…This ranged from the use of advanced instrumentation to the adaptation of adequate culture conditions based on extensive experimental trials conducted before undertaking this study. Briefly, compared with previous instruments available, the instrumentation (Vibratome VT1200; Leica) allows for rapid cutting of each tumor tissue slice in 20-40 s with the significant advantage of controlling the thickness of the slice at a micrometer level (17); it also minimizes the vertical deflection of the blade, and therefore, it preserves the integrity of delicate specimens and ensures a higher number of viable cells on the section surface. In addition, with this technique, no agar or agarose embedding is necessary to successfully cut uneven specimens.…”
Section: Technical Improvements Aimed At Achieving Consistent and Relmentioning
confidence: 99%